2018
DOI: 10.3389/fmicb.2018.02338
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Polysaccharides Inhibit Influenza A Virus Infection—A Promising Natural Anti-flu Drug

Abstract: Influenza A virus causes periodic outbreaks and seriously threatens human health. The drug-resistant mutants have shown an epidemic trend because of the abuse of chemical drugs. Aloe polysaccharides (APS) extracted from Aloe vera leaves have evident effects on the therapy of virus infection. However, the activity of APS in anti-influenza virus has yet to be investigated. Here, we refined polysaccharides from A. vera leaf. In vitro test revealed that APS could inhibit the replication of a H1N1 subtype influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…In silico analysis also revealed that terpene Ginkgolide A can strongly inhibit SARS CoV-2 protease enzyme ( 284 ). Carbohydrates, mainly classified as monosaccharides, disaccharides, polysaccharides, and oligosaccharides ( 282 ), are found as antiviral agent against Human rotavirus, Influenza A virus, HSV-1, HSV-2, Herpes simplex virus (HSV), RSV, Coxsackie B3 Virus, and VSV [( 285 ); Table 4 ]. Acyclovir is an FDA (Food and Drug Administration) approved antiviral drug which is obtained from Carissa edulis ( Supplementary Table 1 ).…”
Section: Plant-based Antiviral Compounds: Group Basis Mechanism Of Acmentioning
confidence: 99%
“…In silico analysis also revealed that terpene Ginkgolide A can strongly inhibit SARS CoV-2 protease enzyme ( 284 ). Carbohydrates, mainly classified as monosaccharides, disaccharides, polysaccharides, and oligosaccharides ( 282 ), are found as antiviral agent against Human rotavirus, Influenza A virus, HSV-1, HSV-2, Herpes simplex virus (HSV), RSV, Coxsackie B3 Virus, and VSV [( 285 ); Table 4 ]. Acyclovir is an FDA (Food and Drug Administration) approved antiviral drug which is obtained from Carissa edulis ( Supplementary Table 1 ).…”
Section: Plant-based Antiviral Compounds: Group Basis Mechanism Of Acmentioning
confidence: 99%
“…According to a review in 2019, acemannan is the major bioactive polysaccharide derived from AV gel [ 49 ]. Acemannan, AV polysaccharides and anthraquinones revealed antiviral activity against the human influenza A virus (H1N1) [ 54 , 55 ]. Hence, acemannan content depends on species and cultivation conditions, irrigation with seawater, harvest season, growth age and solar irradiation intensities [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, plant‐origin polysaccharides have a considerable number of biological activities, such as anti‐inflammatory, anticancer, and antiviral activities, and the virucidal activity of polysaccharides has been the focus of many research studies. As previously reported, the polysaccharide from L. japonica has anti‐EV71 and anti‐RSV activities, but the detailed mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 88%
“…34 Considering their relatively low cytotoxicity, extracts from traditional Chinese medicines or foods show particular advantages and have attracted increasing attention. 35,36 To our knowledge, plant-origin polysaccharides have a considerable number of biological activities, such as antiinflammatory, 22 anticancer, 21 and antiviral activities, 37,38 and the virucidal activity of polysaccharides has been the focus of many research studies. As previously reported, the polysaccharide from L. japonica has anti-EV71 and anti-RSV 24,39 activities, but the detailed mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%